Metazoan parasites of European eel (Anguilla anguilla) from the Koycegiz-Dalyan estuarine channel system, Turkey - (:unkn) unknown (EUR ASSOC FISH PATHOLOGISTS, 2012)
Metazoan parasites of European eel (Anguilla anguilla) were investigated between December 2009 and March 2010 in the Koycegiz-Dalyan estuarine channel system in Turkey. A total of 73 A. anguilla were examined. In two fish (2.7%), no parasites were found. In the others, eight parasite species were found: Pseudodactylogyrus anguillae, Digenea gen. sp., Bucephalus anguillae, Acanthocephalus clavula, Anguillicoloides crassus, Tetraphyllidea gen. sp., Ergasilus gibbus and Ergasilus lime. Most of the eels had two (37.0% of eels), three (31.5%) or one (15.1%) parasite species. Prevalence and mean intensity of the parasite species were: P. anguillae, 82.2%, 24.6; E. gibbus, 52.1%, 4.0; A. crassus, 39.7%, 3.3; E. lizae, 26.0%, 3.4; B. anguillae, 15.1%, 7.5; Digenea gen. sp., 11.0%, 9.0; A. clavula, 6.8%, 1.8; and Tetraphyllidea gen. sp., 1.4%, 3.0, respectively. P. anguillae and B. anguillae are new records for Turkey.
Keywords: FRESH-WATER; COMMUNITIES; CRASSUS; L.; DIVERSITY; BRACKISH